Controlled Pyrolysis of Ni‐MOF‐74 as a Promising Precursor for the Creation of Highly Active Ni Nanocatalysts in Size‐Selective Hydrogenation. Issue 4 (12th December 2017) - Nakatsuka, Kazuki; Yoshii, Takeharu; Kuwahara, Yasutaka; Mori, Kohsuke; Yamashita, Hiromi
Abstract: Metal organic frameworks (MOFs) are a class of porous organic‐inorganic crystalline materials that have attracted much attention as H2 storage devices and catalytic supports. In this paper, the synthesis of highly‐dispersed Ni nanoparticles (NPs) for the hydrogenation of olefins was achieved by employing Ni‐MOF‐74 as a precursor. Investigations of the structural transformation of Ni species derived from Ni‐MOF‐74 during heat treatment were conducted. The transformation was monitored in detail by a combination of XRD, in situ XAFS, and XPS measurements. Ni NPs prepared from Ni‐MOF‐74 were easily reduced by the generation of reducing gases accompanied by the decomposition of Ni‐MOF‐74 structures during heat treatment at over 300 °C under N2 flow. Ni‐MOF‐74‐300 exhibited the highest activity for the hydrogenation of 1‐octene due to efficient suppression of excess agglomerated Ni species during heat treatment. Moreover, Ni‐MOF‐74‐300 showed not only high activity for the hydrogenation of olefins but also high size‐selectivity because of the selective formation of Ni NPs covered by MOFs and the MOF‐derived carbonaceous layer. Abstract : The knights who say Ni : Ni‐MOF‐74 heat‐treated at 300 °C showed high activity and size‐selectivity, due to selective formation of Ni NPs covered by MOFs and a MOF‐derived carbonaceous layer.